Analysis of associations between the TLR3 SNPs rs3775291 and rs3775290 and COVID-19 in a cohort of professionals of Belém-PA, Brazil - Silva, Marcos Jessé Abrahão; Vieira, Marcelo Cleyton da Silva; Souza, Alex Brito; Santos, Everaldina Cordeiro dos; Marcelino, Beatriz dos Reis; Casseb, Samir Mansour Moraes; Lima, Karla Valéria Batista; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Cellular and Infection Microbiology, 2023)
The objective of this article was to verify associations between the SNPs rs3775291 (Cytosine [C]>Thymine [T]) and rs3775290 (C>T) of TLR3 in professionals from Health Institutions (HI) who worked during the first pandemic wave and COVID-19. A case-control study was carried out with workers from HI in Belém-PA, Brazil, divided into symptomatology groups (Asymptomatic-AS, n=91; and Symptomatic-SI, n=121), and severity groups, classified by Chest CT scan (symptomatic with lung involvement – SCP, n=34; symptomatic without lung involvement – SSP, n=8). Genotyping was performed by Sanger sequencing and statistical analysis was performed using the SPSS program. In the analysis of SNP rs3775291, the homozygous recessive genotype (T/T) was not found and the frequency of the mutant allele (T) was less than 2% in the cohort. For the rs3775290 SNP, the frequency of the mutant allele (T) was greater than 42% in the cohort. No significant associations were found for these SNPs in this cohort (N= 212 individuals). The scientific community and physicians can use these facts to find new methods of managing COVID-19.